UJI KARAKTERISTIK PELET REFUSE DERIVED FUEL (RDF) HASIL PROSES PENGOLAHAN SAMPAH MENGGUNAKAN PELLETIZER - DEWI, RANY PUSPITA (Jurusan Teknik Mesin Fakultas Sains dan Teknik Universitas Bangka Belitung, 2025)
Municipal solid waste can be processed into solid fuel in the form of Refuse Derived Fuel (RDF) pellets and used as a fuel substitute. One of them is through the Waste Processing Technology at the Source (TOSS) method. Solid waste generally has a low ash content ranging from 20-40%. RDF is combustible waste or rubbish that goes through a crushing and filtering process by turning it into solid fuel. RDF pellets can be made by pressing using a pellet machine or pelletizer. The aim of this research is to test the characterization of pelletizer performance in processing urban waste into RDF pellets. The characterization tested includes analysis of bound carbon content, volatile content and ash content. The research was carried out by varying the composition of organic waste and inorganic waste, namely 1 sample A (70% organic components + 30% inorganic components), sample B (60% organic components + 40% inorganic components), sample C (50% organic components + 50% inorganic components, sample D (40% organic components + 60% inorganic components), and sample E (30% organic components + 70% inorganic components). The lowest volatile was produced in sample E with a value of 52.8445%, and the lowest ash content was produced in sample A with a value of 4.5466%.